Evaluation of Child Abuse Cases Affected by COVID-19 Pandemic - Aslan, Fatmagül; Timur, Serdar; Pakiş, Işıl (The Bulletin of Legal Medicine, 2020)
Objective: As a result of the measures and restrictions taken in our country during the COVID-19 Pandemic period, it was aimed to analyze the quantitative decrease in the number of cases applied to Antalya Child Monitoring Center and to develop recommendations against its effects. Methods: A total of 309 cases applied to Antalya Center for sexual abuse in 2019 March-April and 2020 March-April were included in the cross-sectional study. Both groups were examined in terms of socio-demographic parameters and evaluations made at the center. Results: 211 cases were evaluated in March-April 2019 and 98 cases were evaluated in March-April 2020 in Antalya Center. The age range of all cases varied between 1-18, and the average age was 12.95 ± 3.24. 257 (83.2%) of the cases were girls. Definitive sexual abuse findings were detected in 225 cases. Considering the reporters and their rates, it was found that the most frequent reporters in the control group were teachers, then parents, while the most frequent reporters in the study group were parents, then teachers. While the ratio of the offender to be lover-friend in the control group was 40.8%, this ratio decreased to 24.5% in the study group.Conclusion: While the risk factors of child sexual abuse increased during the pandemic period, the rate of reporting decreased during the same period. In this study, the role of teachers in reporting abuse was revealed. In terms of multidisciplinary approach among legal and medical professionals, there was no significant difference in this period.
Keywords: Child abuse; pandemic disease; informing; çocuk izlem merkezi; COVID-19